Genetic Interaction of H19 and TGFBR1 Polymorphisms with Risk of Epilepsy in a Chinese Population - Zheng Z; Yan Y; Guo Q; Wang L; Han X; Liu S (Dove Medical Press, 2021)
Zhaoshi Zheng, Yayun Yan, Qi Guo, Libo Wang, Xuemei Han, Songyan Liu No. 1 Department of Neurology, China-Japan Union Hospital of Jilin University, Changchun, Jilin 130031, People’s Republic of ChinaCorrespondence: Xuemei Han; Songyan LiuChina-Japan Union Hospital of Jilin University, Changchun, Jilin 130031, People’s Republic of ChinaTel/Fax +86-431-84679655Email hxm@jlu.edu.cn; Liu_sy@jlu.edu.cnPurpose: Long non-coding RNA H19 was highly expressed in the latent period of epilepsy, contributing to apoptosis of hippocampal neurons by targeting let-7b. Transforming growth factor beta receptor 1 (TGFBR1), a target of let-7b, is located on the susceptibility locus for epilepsy. In this context, we investigated the association between tagSNPs in long non-coding RNA H19 and transforming growth factor beta receptor 1 (TGFBR1) rs6478974 and the risk of epilepsy.Patients and Methods: The present study consisted of 302 patients with epilepsy and 612 age- and gender-matched controls. The polymorphisms were analyzed using a TaqMan allelic genotyping assay. H19 and TGFBR1 mRNA levels were determined using quantitative real-time polymerase chain reaction.Results: The TGFBR1 AT and TT genotypes emerged as a protective factor for the risk of epilepsy (AT vs AA: adjusted OR = 0.59, 95% CI: 0.39– 0.89, P = 0.01; TT vs AA: adjusted OR = 0.53, 95% CI: 0.35– 0.80, P = 0.002, respectively). The protective effect was also observed in recessive genetic model (adjusted OR = 0.56, 95% CI: 0.38– 0.82, P = 0.003). Individuals carrying the rs6478974 TT genotype had lower levels of TGFBR1 mRNA. Moreover, the TCTAT and TCCAA haplotypes emerged as a risk factor for epilepsy and the rs3741219-rs2839698-rs6478974 was associated with an interactive effect on the risk of epilepsy.Conclusion: The current study provides evidence of the rs6478974 TT genotype decreasing the susceptibility to epilepsy by reducing the levels of TGFBR1 mRNA.Keywords: long non-coding RNA H19, transforming growth factor beta receptor 1, genetic susceptibility, quantitative PCR